Perkembangan Ushul Fiqh Di Dunia Kontemporer - Abdulah Pakarti, Muhammad Husni; Farid, Diana; Banaesa, Iba; Nurdin, Rahmat; Abdurrohman, Yusup; Basuni, Ilyas (Al-Syakhsiyyah: Journal of Law & Family Studies, 2023)
Since its introduction at the beginning of Islamic history, Ushul Fiqh has undergone significant developments, especially in facing the increasingly complex challenges of modern times. This study aims to analyze the changes and developments that have occurred in Ushul Fiqh so far, as well as the underlying factors. This research discusses the development of Ushul Fiqh in the contemporary world. Ushul Fiqh is a branch of knowledge in the study of Islamic law that aims to identify the methods and principles used in deriving laws from the sources of Islamic law. The method used is a literature review of various primary and secondary sources, such as classic books of Ushul Fiqh, contemporary literature, and scientific articles. A historical approach and conceptual development analysis were used to understand how Ushul Fiqh has changed over time. The research findings show that Ushul Fiqh underwent adjustments and transformations to address contemporary issues such as technology, human rights, bioethics, economics, and modern finance. One of the main factors influencing the development of Ushul Fiqh in the contemporary world is globalization, which has brought new challenges in interacting with different cultures and legal systems. In addition, social and political changes have also played an important role in shaping Ushul Fiqh's views towards more modern issues. This research provides an in-depth understanding of the development of Ushul Fiqh and its relevance in dealing with the complexities of modern times. It is hoped that this research can make a positive contribution to the development of the science of Ushul Fiqh, inspire further studies, and provide guidance for scholars and practitioners of Islamic law in responding to the challenges of contemporary times.